Co-authorship pair distribution patterns by gender - Ozel, Bulent; Kretschmer, Hildrun; Kretschmer, Theo (Springer, 2014)
This paper examines impact of gender both on publication productivity and on patterns of scientific collaborations in social sciences in Turkey. The research is based on bibliographic data on national level publications in Turkey. It consists of 7,835 papers written by 6,738 scientists. The findings suggest that (1) there are gender differences at publication productivity, participation, presence and contribution; that (2) there are significantly different tendencies at keeping established co-authorship ties for inter-gender and intra-gender pairs; that (3) there are significant regularities exhibited by coauthor pairs based on each partner author's publication productivity and findings further show that (4) regularities are different for inter-gender and intra-gender co-authorships. This study contributes to literature by exemplifying an integrated approach to better examine role of gender in scientific collaborations. In addition to descriptive social network analysis methods, it exploits and adopts parametric models from the literature: (1) Social Gestalt theory, a model based on bi-variate distributions of co-author pairs' frequencies; (2) Lotka's power law distribution on publication productivity of single authors; (3) Power law distributions of co-author pairs' frequencies.
Keywords: Collaboration İn Sciences; Gender; Co-Authorship Networks; Interpersonal Attraction; Social Gestalt Model; Research Collaboration; Coauthorship